Learn to program with Minecraft plugins Create flaming cows in Java using CanaryMod - Hunt, Andrew (Pragmatic Bookshelf, 2014)
Write your own Minecraft plugins and watch your code come to life with flaming cows, flying creepers, teleportation, and interactivity. You'll learn how to code and build plugins for your own Minecraft game using Java and the CanaryMod library and server. You'll learn Java programming, backup your code using Git, and set up and run your own server. By the end of the book you'll be able to design and code your own plugins from scratch.